THE TRADITION OF THE HEAD OF THE EARTH (Ethnography Study of Symbolic Meaning of Nyadran Earth Tradition in Songowareng Village, Bluluk Sub-district, Lamongan District) - Susanto, Agus; Siswanto, Budi; Jatmikowati, Sri Hartini (IJRDO - Journal of Social Science and Humanities Research, 2017)
The objectives of the study are to describe and analyze the background of earth nyadran tradition, the socio-cultural values of the earth nyadran tradition, and the symbolic meaning contained in the earth nyadran tradition in Songowareng village, Bluluk sub-district, Lamongan regency. Type of descriptive qualitative research with grounded theory method. In determining the informant using purposive sampling technique. Data analysis techniques using the ethnography developed by Spradley. The results of the research: First, the tradition of earth nyadran is held once a year after the rice harvest season for two days and two nights, precisely on Saturday Pon and Ngat Wage, as a form of gratitude to God for the success of rice harvest. Secondly, the socio-cultural values contained in the preparation stage include the formation of the committee, the implementation of nguras sendang, and the cleansing of ancestral graves, and in the implementation stage includes the activities of salvation in sendang and entertainment art of tayub. Thirdly, the symbols contained in the event of earth nyadran tradition are contained in uborampe ambeng, cok will and gending heirlooms are gending eling-eling, rangu-rangu, gonggo mino, genderuwo momong, boar strikes, bondo boyo and angkleng, each has its own meaning and hasvalue for the people of Songowareng village.